(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
This research aimed to investigate human behavior under concurrent variable interval, variable interval schedules of reinforcement manipulating variables other than verbal behavior. Four undergraduate students were exposed to five conditions with different concurrent pairs. A PC computer with touch screen programmed sessions and recorded responses. Every five reinforcers the session stopped, and the participants had to report how to win points. The results showed that time and response distributions were in accordance to contingencies, although none of the participants described the rule. Although experimental literature have affirmed that human behavior in concurrent schedules does not show matching in response distribution due to subjects verbal behavior as the critical variable in differences between humans and non-humans, the present study showed that matching is a matter of procedure, not due to rule formulation.